Securitizing UNRWA A Discourse-Historical Analysis of Israeli Leaders’ Discourse on UNRWA - Kwoska,Eliza (2025)
This thesis examines how Israeli political actors discursively construct and delegitimize the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) on the social media platform X between October 7, 2023, and January 29, 2025. Through a Discourse-Historical Approach (DHA), this study examines how UNRWA is framed as a security threat, embedded within broader ideological projects of state legitimacy, national identity, and settler coloniality. The analysis draws on Securitization Theory, the concept of ontological (in)security, and biopolitical thought. The analysis focuses on Israeli communication on X, exploring how political discourse is employed to delegitimize UNRWA by portraying it as a threat to Israel's security. This framing serves to question the agency's role and justify calls for its dismantlement, while reinforcing dominant Israeli narratives and consolidating its political discourse. By uncovering these discursive strategies, the study reveals how language functions as a tool of power within the settler-colonial context, shaping perceptions and sustaining structures of control over Palestinian life.
Keywords: Israel; UNRWA; Palestine; securitization; Discourse-Historical Approach